BASIC MEDICAL SCIENCES AND PROBLEM-BASED LEARNING: PITFALLS AND POSSIBLE IMPROVEMENT FROM THE PERSPECTIVE OF TEACHERS AND STUDENTS - Teuku Renaldi; Said Usman; Maimun Syukri; Sofia Sofia; Dedy Syahrizal (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Basic medical sciences are essential foundation for the constructive learning of clinical sciences. Faculty of Medicine, Universitas Syiah Kuala is currently implementing Problem-based learning (PBL) for basic medical sciences. Studies have been conducted in many places with inconsistently different results that it is impossible to draw theoretical and practical conclusions regarding the implementation of PBL for basic medical sciences. This study aimed to evaluate the implementation of PBL for basic medical sciences at Faculty of Medicine, Universitas Syiah Kuala from the perspectives of pre-clinical teachers, clinical teachers and medical students.Methods: This is a qualitative study with a phenomenological approach. Respondents were pre-clinical teachers, clinical teachers and medical students. Data collection were carried out by using focused-group discussion (FGD). Data analysis was carried out qualitatively by using thematic analysis.Results: This study identified three themes: (1) integrated thematic blocks are not adequate for the learning of basic medical sciences, (2) inadequacy of basic medical sciences practice activities, and (3) possible improvements through curriculum revision.Conclusion: The implementation of PBL in the form of integrated blocks for basic medical sciences is not adequately constructive to prepare students to learn clinical sciences. Hybrid curriculum which incorporates conventional methods for basic medical sciences and PBL for clinical sciences is recommended to improve students’ constructive learning. Further studies on hybrid curriculum is needed to evaluate its effect of basic medical sciences. Keywords: Basic medical sciences, Problem-based learning (PBL), practical session, hybrid curriculum, constructive learning, self-directed learning.